Nursing striped catfish (Pangasianodon hypophthalmus) with 2 stages from larvae to fingerlings : - Pham, Nguyen Duy (Can Tho University, 2020)
Mekong Delta of Vietnam is famous for the culture and production of the striped catfish (Pangasianodon hypophthalmus) and is considered as the important aquaculture species because of its easy rearing, fast-growing and high production. However, the rearing of the larvae and the fingerlings in the nursing phase had been a tough ask due to a very poor survival rate and growth. The blooming of the pangasius industry and increasing culture area has asked for more and more seeds every year. To find the best stocking density of the larvaean experiment was carried out in two phases. The first phase was nursing of the 24 hours old larvae in a PV lined earthen pond for 45 days until it reaches fingerlings size. And the second phase of the experiment was to determine the appropriate stocking density with the highest survival rate by rearing larvae for 75 days in a concrete tank until fingerlings size. Three treatments of stocking density 750 tails/m², 1000 tails/m², and 1200 tails/m² were cultured in an earthen pond lined by PV of area 200m². For the second phase, three treatments with three replication of the stocking density 200 tails/m³, 300 tails/m³, and 400 tails/m³ were reared in a concrete tank of volume 25m³.